2015
DOI: 10.1080/13548506.2015.1127395
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depressive symptoms and its correlates among medical students in China: a national survey in 33 universities

Abstract: We conducted a national survey among medical students in China to estimate the prevalence of depressive symptoms and explore associated risk factors based on an established questionnaire composed of demographic information, life events in the past four weeks before survey, and the validated Chinese version of the 21-item Beck's Depression Inventory (BDI). The mean age of enrolled 9010 students was 20.7 (standard deviation: 1.6) years. BDI scores indicated that 19.9% had depressive symptoms based on the cut-off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 24 publications
2
39
2
4
Order By: Relevance
“…Overall, 19% of the respondents in our sample were depressed by accepted BDI cutoffs. Compared to studies done in the region using BDI, this is similar to China (19% depression) (Pan et al, 2016) while lower than the results of both Hong Kong (48%) (Chan, 1991) and India (45%) (Gupta & Basak, 2013). However, both Chan (1991) and Gupta and Basak (2013) used a lower cut-off score to diagnose depression.…”
Section: Discussioncontrasting
confidence: 55%
“…Overall, 19% of the respondents in our sample were depressed by accepted BDI cutoffs. Compared to studies done in the region using BDI, this is similar to China (19% depression) (Pan et al, 2016) while lower than the results of both Hong Kong (48%) (Chan, 1991) and India (45%) (Gupta & Basak, 2013). However, both Chan (1991) and Gupta and Basak (2013) used a lower cut-off score to diagnose depression.…”
Section: Discussioncontrasting
confidence: 55%
“…In China, the 3rd and 4th year of the medical course is an important transitional stage in the student's academic calendar which is characterized by the heaviest study load and the full-time clinical exposure. The incidence of depression was proven to be higher in senior medical students by a national survey that has screened 33 universities in China [19]. Hence, we selected the 3rd/4th grade medical students as the participants in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In China, medical students usually spend ve years in their undergraduate course with initiation of full clinical contact in their third year. This transition always brings the heaviest study load and most of the associated mental problems [19]. Students in senior grades often feel more depressed than their junior grade students with more burnout as well as lower sense of personal achievement [20].…”
Section: Introductionmentioning
confidence: 99%
“…The focus of this paper is on the symptoms of depression and anxiety experienced by medical students. Studies of undergraduate medical students, undertaken in different countries, suggest that students experience increasing mental health issues including symptoms of depression and anxiety as their course progresses [11,12]. However other studies have found higher levels of depression and anxiety among medical students at the outset of their course [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…For example female students in Serbia and Pakistan were found to record significantly higher levels of both depression and anxiety but gender differences for anxiety were more pronounced than those for depression [18,19]. By contrast, a study of Chinese medical students found a significantly higher proportion of male students had symptoms of depression compared to female students [12].…”
Section: Introductionmentioning
confidence: 99%